KONFLIK PEMERINTAH ADAT DAN PEMERINTAH NAGARI DALAM PENGELOLAAN PASAR TRADISIONAL DI NAGARI DUO KOTO - Syamsul Hidayat; Nursyirwan Nursyirwan; Ediwar Ediwar (Journal of Innovation Research and Knowledge, 2023)
Conflict is one of the social phenomena that occurs in market development. Conflicts can occur as a result of revitalization, development or rejuvenation carried out by the government or market managers. Such a conflict occurred between the Nagari Duo Koto Government and the Traditional Government (KAN Duo Koto) regarding the construction of an acaic market in Nagari Duo Koto. The researcher chose to conduct this research because the hegemony of power between the traditional government and the nagari government in market management has caused conflict, thereby hampering the implementation of market development. The problem in this research is what forms of conflict issues and behavior and the causes of conflict between the Traditional Government and the Nagari Government. Apart from that, this research problem also explains how to resolve conflicts between these two equal institutions. To look at this problem, researchers used Ralph Dahrendorf's conflict theory which explains that conflict between power holders shows the existence of unequal power and a malfunction of the rescue valve. The method used is a qualitative method which is descriptive analysis with two data collection techniques, namely in-depth interviews and supported by data documentation. From the results of the analysis, it was concluded that conflict issues emerged and developed related to market development programs not being implemented, and power holders disagreeing in understanding the applicable laws. The causes of the conflict between KAN and the Nagari Government are the existence of interest factors in the implementation of market development, the failure of the rescue valve in the conflict that occurs, gaps in structure or understanding of information, and the mismatch between formal and informal environments which are also causes of conflict. The conclusion from the results of this research is that Ideas and notions that contain various interests in the implementation of village funds in market development are the main cause of conflict.